Dipeptidyl peptidase 4 (DPP-4) inhibitors and the risk of lung cancer: current evidence and future directions. Issue 1 (2nd January 2023) - Singh, Harmanjit; Sharma, Jatin; Sikarwar, Pallavi; Kakkar, Ashish Kumar
ABSTRACT: Introduction: Recent evidence has linked long-term use of angiotensin converting enzyme (ACE) inhibitors with the risk of developing lung cancer by increasing levels of substance P (SP) and bradykinin in lung tissue. DPP-4 inhibitors, by virtue of their mechanism of action, may increase the level of SP and pose a similar risk of incident lung cancer. Concomitant use of DPP-4 inhibitors and ACE inhibitors may further exaggerate this plausible risk. Area covered: Here we discuss both direct and indirect evidence involving mechanisms by which DPP-4 inhibitors may increase the risk of lung cancer in treated patients. We highlight that increased levels of SP with DPP-4 inhibitor monotherapy and raised levels of both SP and bradykinin with add-on ACE inhibitor therapy may further enhance this risk. Expert opinion: DPP-4 inhibitors are prescribed in type-2 diabetes mellitus patients with or without cardiovascular disease. When used together, ACE inhibitors and DPP-4 inhibitors may act synergistically and further amplify the lung cancer risk. Consequently, physicians should consider this plausible association while prescribing them concomitantly especially in high-risk individuals. Well-planned research studies are required to assess the association of DPP-4 inhibitors with lung cancer and other adverse effects linked to increased levels of SP and bradykinin.